2012
DOI: 10.1523/jneurosci.4122-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Frequency Phase–Phase Coupling between Theta and Gamma Oscillations in the Hippocampus

Abstract: Summary Neuronal oscillations allow for temporal segmentation of neuronal spikes. Interdependent oscillators can integrate multiple layers of information. We examined phase-phase coupling of theta and gamma oscillators in the CA1 region of rat hippocampus during maze exploration and REM sleep. Hippocampal theta waves were asymmetric, and estimation of the spatial position of the animal was improved by identifying the waveform-based phase of spiking, compared to traditional methods used for phase estimation. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

89
777
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 729 publications
(890 citation statements)
references
References 88 publications
89
777
2
4
Order By: Relevance
“…The observation that ACC/ PFC circuits theta-synchronized the activation at a low-gammafrequency band is, to our knowledge, unprecedented in LFP recordings in the primate brain. However, a similar theta to low-gamma P-A correlation has been found in rodents to emerge in medial frontal, entorhinal, and hippocampal circuits (8,26,27,31). In the cortex of nonhuman primates, synchronization of a low (35-55 Hz) gamma-frequency band has recently been described to characterize local LFP and spike-LFP coherence within the macaque frontal eye field (FEF) during sustained selective attention (32) (for a lower 30-to 40-Hz beta/ gamma in LPFC, see ref.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The observation that ACC/ PFC circuits theta-synchronized the activation at a low-gammafrequency band is, to our knowledge, unprecedented in LFP recordings in the primate brain. However, a similar theta to low-gamma P-A correlation has been found in rodents to emerge in medial frontal, entorhinal, and hippocampal circuits (8,26,27,31). In the cortex of nonhuman primates, synchronization of a low (35-55 Hz) gamma-frequency band has recently been described to characterize local LFP and spike-LFP coherence within the macaque frontal eye field (FEF) during sustained selective attention (32) (for a lower 30-to 40-Hz beta/ gamma in LPFC, see ref.…”
Section: Discussionsupporting
confidence: 70%
“…4). In previous studies, 5-to 10-Hz activity fluctuations were shown to organize distinct band-limited gamma-frequency bands categorized as low (∼35-55 Hz), medium (∼50-90 Hz), and high (epsilon; ∼90-140 Hz) bands, each likely originating in separable underlying circuit motifs (8,11,26). The observation that ACC/ PFC circuits theta-synchronized the activation at a low-gammafrequency band is, to our knowledge, unprecedented in LFP recordings in the primate brain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The frequency of these oscillations proved to be modulated by experimental manipulations of the size and duration of the IPSPs as predicted by computer simulations (Whittington et al, 1995). Inhibitory neurons also play a key role in pacing faster physiological activity, in the ripple band 80-250 Hz, as shown by unit recordings in vivo (Ylinen et al, 1995): as mentioned above the distinction between γ and ripples is less clear that it once seemed (Belluscio et al, 2012;Crone et al, 2006;Edwards et al, 2005;Sullivan et al, 2011). However, prolonged highfrequency oscillations based exclusively on synaptic mechanisms are unlikely because neurotransmitter depletion will lead to a strong synaptic depression and thus to termination of these oscillations (Zucker and Regehr, 2002).…”
Section: Network Oscillatorsmentioning
confidence: 88%
“…However, we will review some aspects of γ oscillations, partly because they shed some light on HFO mechanisms, and partly because there can be overlap between γ and "ripples", a transient hippocampal HFO in the 100 Hz to 200-250 Hz band. Functionally γ and ripples can coexist under physiological conditions and share mechanisms (Sullivan et al, 2011), or can be linked under the term fast γ (90-150 Hz, with slow γ at 30-50 Hz and mid γ 50-90 Hz) (Belluscio et al, 2012), while other authors call oscillations from ~60 to 200-250 Hz "high γ" (Crone et al, 2006;Edwards et al, 2005).…”
Section: Introductionmentioning
confidence: 99%